2019
DOI: 10.3390/ijerph16050715
|View full text |Cite
|
Sign up to set email alerts
|

Response of Freshwater Biofilms to Antibiotic Florfenicol and Ofloxacin Stress: Role of Extracellular Polymeric Substances

Abstract: Antibiotic residues have been detected in aquatic environments worldwide. Biofilms are one of the most successful life forms, and as a result are ubiquitous in natural waters. However, the response mechanism of freshwater biofilms to the stress of various antibiotic residues is still unclear. Here, the stress of veterinary antibiotic florfenicol (FF) and fluoroquinolone antibiotic ofloxacin (OFL) on freshwater biofilms were investigated by determining the changes in the key physicochemical and biological prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Increased biofilm may be a response to stress detected through the inhibition of growth, and antibiotic concentrations causing greatest stress will likely be close to those arresting growth completely (Bernier & Surette, 2013). Bacteria in biofilms are better protected against environmental insults such as antibiotics, as far greater concentrations are needed to kill cells in a biofilm compared with a planktonic existence (Davey & O’Toole, 2000; Olsen, 2015; Olson, Ceri, Morck, Buret, & Read, 2002), while increased production of extracellular polymeric substances by bacteria growing in a biofilm provides one explanation because this can bind antibiotics to prevent penetration into the biofilm structure (Mulcahy, Charron‐Mazenod, & Lewenza, 2008; Olsen, 2015; Wang et al., 2019). Bacteria growing in biofilms show other alterations in behaviour and gene expression that can further explain decreased susceptibility to antibacterial agents including reduced metabolism (Knudsen, Fromberg, Ng, & Gram, 2016; Olsen, 2015; Song et al., 2016; Sun, Chen, Lin, & Lin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increased biofilm may be a response to stress detected through the inhibition of growth, and antibiotic concentrations causing greatest stress will likely be close to those arresting growth completely (Bernier & Surette, 2013). Bacteria in biofilms are better protected against environmental insults such as antibiotics, as far greater concentrations are needed to kill cells in a biofilm compared with a planktonic existence (Davey & O’Toole, 2000; Olsen, 2015; Olson, Ceri, Morck, Buret, & Read, 2002), while increased production of extracellular polymeric substances by bacteria growing in a biofilm provides one explanation because this can bind antibiotics to prevent penetration into the biofilm structure (Mulcahy, Charron‐Mazenod, & Lewenza, 2008; Olsen, 2015; Wang et al., 2019). Bacteria growing in biofilms show other alterations in behaviour and gene expression that can further explain decreased susceptibility to antibacterial agents including reduced metabolism (Knudsen, Fromberg, Ng, & Gram, 2016; Olsen, 2015; Song et al., 2016; Sun, Chen, Lin, & Lin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that bioelectrochemical systems such as microbial fuel cells are capable of degrading different pharmaceuticals. Amongst these are ampicillin [11] , sulphonamides [37] , Florfenicol and Ofloxacin [38] . Reports by Zhou et al [39] on the electrochemical responses of antibiotics addition to MFCs with developed anode showed that lower concentration of antibiotics resulted in greater power generation, whilst higher concentrations generated at slightly lower voltage levels.…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae possess a large number of enzymes that play a role in cellular protection through the deactivation and/or degradation of a range of organic compounds that induce cellular stress in microalgae . Microalgal degradation of ECs relies on a complex enzymatic process involving a number of enzymes, including: superoxide dismutase, catalase, glutamyl-tRNA reductase, malate/pyruvate dehydrogenase, mono(di)oxygenase, pyrophosphatase, carboxylase/decarboxylase, dehydratase, alkaline and acid phosphatase, transferase, and hydrolases (Elbaz et al, 2010;Xiong et al, 2018;Wang et al, 2019). Several of these enzymes, including superoxide dismutase and catalase, have shown increased activity in several freshwater microalgal species, when the cells were exposed to the veterinary antibiotics Florfenicol and Ofloxacin .…”
Section: Algal Biodegradation Of Emerging Contaminantsmentioning
confidence: 99%